Dental caries and its relationship to bacterial infection, hypoplasia, diet, and oral hygiene in 6- to 36-month-old children - Milgrom P, Riedy CA, Weinstein P, Tanner ACR, Manibusan L, Bruss J (Blackwell Synergy, 2000)
Caufield et al. (1) have suggested that the acquisition of mutans streptococci in young children most likely takes place during a ‘‘window of infectivity’’ from 19 to 31 months of age. Objectives and Methods: This study determined the prevalence of dental caries and bacterial infection in a randomly selected sample of 199 children 6 to 36 months old from the island of Saipan in the Commonwealth of the Northern Mariana Islands, USA.